TEACHING VOCABULARY BY USING SUBSTITUTION AND CUED RESPONSE DRILLS TECHNIQUE TO THE EIGHTH GRADE STUDENTS OF SMP NEGERI 41 MEDAN - Situmorang, Romasta; Raja, Viator Lumban; Ginting, Fiber Yun Almanda (Kairos English Language Teaching Journal, 2020)
In learning a language, the first thing people should learn is vocabulary. Vocabulary is one of the essential aspects of language.Â Without vocabulary nothing can be conveyed.Â In other words, vocabulary is the core of the language itself.Â The aim of this study is to find out whether or not Substitution and Cued Response Drills Technique gives improvement on studentsâ€™ vocabulary mastery.Â The subject of the study is the students of Class VIII E of SMP Negeri 41 Medan in the Academic Year of 2017/2018.Â Vocabulary test, questionnaire, observation sheet and field notes were used as the instruments for collecting data. The results of the study showed the improvement of the studentsâ€™ vocabulary mastery.Â It is proven by the studentsâ€™ mean score of each test: pre test is 45.37, formative test is 58.28 and post test is 70.12.Â Moreover, the improvement could also be seen from the Minimum Mastery Criteria (Kriteria Ketuntasan Minimum) that showed the percentage of studentsâ€™ score of pre test is 9.37%, formative test is 31.25%, and post test is 56.25%.Â It can be concluded that there is a progress on student score percentage namely 46.88% from pre-test to post-test based on KKM. Therefore, the application of Substitution and Cued Response Drills Technique is suitable to teach vocabulary to the students.